An evaluation of the First Parent Health Visitor Scheme. Issue 3 (1st March 2002) - Emond, A; Pollock, J; Deave, T; Bonnell, S; Peters, T J; Harvey, I
Abstract : Aims: To assess outcomes in families who received the First Parent Health Visitor Scheme (FPHVS), in comparison with families who received conventional ("generic") health visiting. Methods: Retrospective data on 2113 families were collected during 1986–92 as part of National Health Service (NHS) service provision. Prospective data were collected during 1993–98 on 459 mothers and their children, with outcomes assessed at one year (93% follow up) and two years (80% follow up). Results: There were no differences between the groups of mothers in self esteem, locus of control, or depression rates. The women who received the FPHVS were more likely to have changed partners, but they also had a wider support network than comparison women, and consulted their general practitioner (GP) less often. Breast feeding rates were higher in the FPHVS mothers, who also gave their infants more fruit juice drinks than the comparison group. No differences were apparent in developmental outcome using the Bayley Scales at 1 and 2 years of age. Both height and weight Z scores at 2 years of age were lower in the FPHVS children than the comparison children. Receipt of the FPHVS was associated with increased use of electric socket covers and lower accident rates in the second year of life. No differences were seen in immunisation rates, uptake of child health surveillance, or use of hospital services. A higher proportion of families who received the FPHVS were registered on the local child protection register compared with comparison families. Conclusion: Clustering effects dominated the analysis, but overall this evaluation could not show a clear advantage for the FPHVS over conventional health visiting.